In vitro pharmacological activities and GC-MS analysis of different solvent extracts of Lantana camara leaves collected from tropical region of Malaysia - Swamy, Mallappa Kumara; Sinniah, Uma Rani; Akhtar, Mohd. Sayeed (Hindawi Publishing Corporation, 2015)
We investigated the effect of different solvents (ethyl acetate, methanol, acetone, and chloroform) on the extraction of phytoconstituents from Lantana camara leaves and their antioxidant and antibacterial activities. Further, GC-MS analysis was carried out to identify the bioactive chemical constituents occurring in the active extract. The results revealed the presence of various phytocompounds in the extracts. The methanol solvent recovered higher extractable compounds (14.4% of yield) and contained the highest phenolic (92.8 mg GAE/g) and flavonoid (26.5 mg RE/g) content. DPPH radical scavenging assay showed the IC50 value of 165, 200, 245, and 440 μg/mL for methanol, ethyl acetate, acetone, and chloroform extracts, respectively. The hydroxyl scavenging activity test showed the IC50 value of 110, 240, 300, and 510 μg/mL for methanol, ethyl acetate, acetone, and chloroform extracts, respectively. Gram negative bacterial pathogens (E. coli and K. pneumoniae) were more susceptible to all extracts compared to Gram positive bacteria (M. luteus, B. subtilis, and S. aureus). Methanol extract had the highest inhibition activity against all the tested microbes. Moreover, methanolic extract of L. camara contained 32 bioactive components as revealed by GC-MS study. The identified major compounds included hexadecanoic acid (5.197%), phytol (4.528%), caryophyllene oxide (4.605%), and 9,12,15-octadecatrienoic acid, methyl ester, (Z,Z,Z)- (3.751%).